Analisis pola asuh orang tua terhadap tanggung jawab belajar anak kelas 4 SD Negeri Koripandriyo Gabus Pati pada masa pandemi covid-19 - Fitria Putri Charisma; Nur Fajrie; Erik Aditia Ismaya (IKIP Siliwangi, 2023)
This study aims to analyze the parenting patterns of students towards the learning responsibilities of 4th graders at Koripandriyo State Elementary School during the covid-19 pandemic. Parenting pattern is the relationship between parents and children in providing care that is carried out consistently from birth to adolescence. This study uses a qualitative descriptive method, located at Koripandriyo State Elementary School, which is located in Koripandriyo Village, Gabus District, Pati Regency with the research subjects being children and parents in grade 4. This study uses data collection techniques of observation, interviews, documentation and recording. The data analysis technique used is descriptive qualitative data analysis technique. The results of this study show that there are three forms of parenting for grade 4 students at Koripandriyo State Elementary School during the Covid-19 pandemic, namely authoritarian, democratic, and permissive. It was recorded that out of 25 students, there were 1 authoritarian parenting, 20 democratic parenting, and 4 permissive parenting styles. Authoritarian parenting parents perform 5 or more of the nine indicators of authoritarian parenting. Democratic parenting parents perform 6 or more of the eleven indicators of democratic parenting. Permissive parenting parents perform 6 or more than ten indicators of permissive parenting. It is important for future researchers to explore more about the factors that influence parenting styles of Koripandriyo Elementary School students, especially those in the authoritarian and permissive form in order to find the root of the problem and at the same time the solution.